Irreversible electroporation in primary and metastatic hepatic malignancies: A review. Issue 17 (April 2017) - Lyu, Tianchu; Wang, Xifu; Su, Zhanliang; Shangguan, Junjie; Sun, Chong; Figini, Matteo; Wang, Jian; Yaghmai, Vahid; Larson, Andrew C.; Zhang, Zhuoli
Abstract: Background: Liver cancer makes up a huge percentage of cancer mortality worldwide. Irreversible electroporation (IRE) is a relatively new minimally invasive nonthermal ablation technique for tumors that applies short pulses of high frequency electrical energy to irreversibly destabilize cell membrane to induce tumor cell apoptosis. Methods: This review aims to investigate the studies regarding the use of IRE treatment in liver tumors and metastases to liver. We searched PubMed for all of IRE relevant English language articles published up to September 2016. They included clinical trials, experimental studies, observational studies, and reviews. This review manuscript is nothing with ethics issues and ethical approval is not provided. Results: In recent years, increasingly more studies in both preclinical and clinical settings have been conducted to examine the safety and efficacy of this new technique, shedding light on the crucial advantages and disadvantages that IRE possesses. Unlike the current leading thermal ablation techniques, such as radiofrequency ablation (RFA), microwave ablation (MWA), and cryoablation, IRE requires shorter ablation time without damaging adjacent important vital structures. Conclusion: Although IRE has successfully claimed its valuable status in the field of hepatic cancer treatment both preclinical and clinical settings. In order to systemically test and establish its safety and efficacy for clinical applications, more studies still need to be conducted.